2019
DOI: 10.1155/2019/7074264
|View full text |Cite
|
Sign up to set email alerts
|

A Color-Image Encryption Scheme Using a 2D Chaotic System and DNA Coding

Abstract: This paper proposes a method of encrypting images with password protection for secure sharing based on deoxyribonucleic acid (DNA) sequence operations and the tangent-delay ellipse reflecting the cavity-map system (TD-ERCS). The initial values of the TD-ERCS system are generated from a user’s password, and the TD-ERCS system is used to scramble the pixel locations of the R, G, and B matrices of the original image. Next, three DNA-sequence matrices are generated by encoding the permuted color image such that it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…However, they fail to protect the image against transmission noise, which can be introduced during the transmission process of image. 1 In cryptography, actual data is converted to meaningless form. To protect images, image encryption algorithms are vital.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they fail to protect the image against transmission noise, which can be introduced during the transmission process of image. 1 In cryptography, actual data is converted to meaningless form. To protect images, image encryption algorithms are vital.…”
Section: Introductionmentioning
confidence: 99%
“…AES, International Data Encryption Algorithm (IDEA) and DES are some traditional block encryption approaches that can only encrypt images effectively to certain extent. However, they fail to protect the image against transmission noise, which can be introduced during the transmission process of image 1 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA computing algorithm has advantages which include high parallelism, ultra-low power consumption and big information density. So, image encryption combined with the DNA computing algorithm and the chaotic map is born which is used to solve this problem [34][35][36][37][38][39][40][41][42][43][44][45]. An image encryption based on dynamic DNA encoding was proposed by Aditya et al [34].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a new area of DNA image encryption has emerged. With the application of DNA addition, subtraction, XOR, and complementation in the field of image encryption, researchers found that an encryption system based on chaotic systems and DNA computing is easier to implement while ensuring image security [19][20][21][22][23][24][25][26]. For example, Chai al.…”
Section: Introductionmentioning
confidence: 99%